2015
DOI: 10.1016/j.earlhumdev.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Deficient maternal zinc intake—but not folate—is associated with lower fetal heart rate variability

Abstract: Objective Few studies of maternal prenatal diet and child development examine micronutrient status in relation to fetal assessment. Methods Twenty-four-hour dietary recall of zinc and folate and 20min of fetal heart rate were collected from 3rd trimester pregnant adolescents. Results Deficient zinc was associated with less fetal heart rate variability. Deficient folate had no associations with HRV. Neither deficient zinc nor deficient folate was related to fetal heart rate. Conclusions These findings, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
1
5
0
1
Order By: Relevance
“…Additionally, MUN rats did not show an elevated HR, which was detected in the SHR model. The lack of HR alterations of MUN rats is in line with other studies using maternal low protein [ 35 , 86 ] or low micronutrients, such as zinc [ 87 ] or vitamin B12 [ 88 ] diets during pregnancy. In SHR, the tachycardia probably reflects an alteration in baroreceptor regulation, as previously reported [ 86 ], which may contribute to the higher blood pressure in this strain.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, MUN rats did not show an elevated HR, which was detected in the SHR model. The lack of HR alterations of MUN rats is in line with other studies using maternal low protein [ 35 , 86 ] or low micronutrients, such as zinc [ 87 ] or vitamin B12 [ 88 ] diets during pregnancy. In SHR, the tachycardia probably reflects an alteration in baroreceptor regulation, as previously reported [ 86 ], which may contribute to the higher blood pressure in this strain.…”
Section: Discussionsupporting
confidence: 88%
“…A second possible underlying process is increased uterine artery resistance and the limited blood flow to the fetus (e.g., O'Donnell et al, 2009). Inadequate prenatal care and less healthy habits associated with depression can also affect fetal neurobehavioral maturity (e.g., Monk, Georgieff, & Osterholm, 2013;Nordentoft et al, 1996;Spann et al, 2015). The limitations of this study include the self-reported prenatal depression.…”
Section: Discussionmentioning
confidence: 94%
“…Also maternal infections, diabetes, and toxicant exposures that stimulate an acute-phase response causes a decreased transport of zinc to the developing fetus (Nuttall et al, 2017 ), which can lead to increased risk of NTDs (Chua et al, 2006 ; Uriu-Adams and Keen, 2010 ). On the other hand, a marginally low dietary zinc intake during pregnancy is associated with decreased fetal heart rate variability, suggesting impaired regulation of the autonomic nervous system (Spann et al, 2015 ). Accordingly, prenatal zinc supplementation improves the regulation of the autonomic nervous system later in life (Caulfield et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%